Wykorzystanie złóż tarczowych do usuwania azotu amonowego w warunkach ograniczonego dostępu tlenu = Removal of ammonium nitrogen under low oxygen concentration using rotating contactor - Nowak, Rafał; Włodarczyk-Makuła, Maria (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article presents results of research on ammonia nitrogen removal efficiency under low oxygen concentration using rotating contractor. Synthetic wastewater with an increasing level of ammonium nitrogen (250 and 500 mg N-NH4 +/dm3) and rotating contactors inhabited by nitrifying bacteria were used during the study.
Keywords: azot amonowy; niskie stężenie tlenu; złoża tarczowe; ammonium nitrogen; low oxygen concentration; rotating contactor